The Reform of Engineering Professional Online Education Courses by Artificial Intelligence and Wireless Network Technology in the Context of Engineering Certification. (18th February 2022) - Che, Chang; Luo, Qiubin; Mao, Yan
Abstract : The problems existing in the online education courses of engineering majors in colleges and universities are studied, and the online education platform under the background of engineering certification is designed and researched. Artificial intelligence (AI) technology and wireless network technology are used in the in-depth study of online education courses. In terms of AI, the storage of data is specifically divided into three levels, namely, the source layer (operational data layer), the historical storage layer, and the data model layer. Data analysis includes the total number of data, spatial scope, and period, etc. The results show that the overall response time of the designed platform to the operation of university teachers and students is controlled within 3 s. The test results of two online education platforms show that the performance of the designed online education platform is relatively stable. It provides hardware support for online curriculum reform. In addition, in terms of the platform test pass rate, after many tests, the online education platform security test pass rate is above 98%. In the end, these conclusions are drawn: AI technology and wireless network technology can effectively improve the performance of online education platforms. Meanwhile, this can also further improve the learning efficiency of online education courses for college engineering students.